REDD+, Conservation, and Conversion - Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2018)
The effectiveness of periodical payment for forested lands as an incentive system to stop a conversion of forested lands is analyzed. Four simple models are outlined and analyzed to investigate behavior of the land manager whether to maintain the lands remain forested or to convert them to other uses. The analysis is pure theoretical employing the optimal control theory. A key element to induce the land manager to adopt forest conservation rather than forest conversion is a combination of periodical payments for the forested lands and the desirable scrap value. Without the desirable scrap value, periodical payments of carbon stock, regardless of the tariff, cannot stop the conversion; the tariff affects only the time when the conversion will be conducted but it is not sufficient to induce the land manager not to convert the forested lands. On the basis of this analysis, then policy implication is outlined. In order to provide the desirable scrap value, then a policy change is required. However, its implementation very likely encounters serious challenges from the land manager.